Effect of heat treatment conditions on the fatigue resistance of press hardened 22MnB5 steel evaluated through rapid testing technique. Issue 1 (June 2021) - Parareda, S.; Casellas, D.; Frómeta, D.; Garcia-Llamas, E.; Lara, A.; Pujante, J.; Mateo, A.
Abstract: Fatigue strength is considered as a crucial parameter for automotive applications subjected to cyclic loads during their long service life, as chassis parts. The high yield stress of press hardened steels poses them as good candidates for lightweight solutions with improved fatigue resistance. However, their high strength leads to an increase in notch sensitivity which can ruin the whole part's integrity. This behaviour was observed in previous works on press hardened steels, where their high fatigue strength was significantly affected by the surface conditions and by heat treatment conditions. Nevertheless, press hardening steels are still good candidates to manufacture complex geometry parts reaching high performance. Aiming at increasing the existing knowledge on the fatigue behaviour of press hardened steels, this paper analyses the fatigue performance of boron steel (22MnB5) under different time austenitizing times. Fatigue resistance is evaluated using a novel rapid fatigue testing technique based on the stiffness evolution. The method permits a fast and reliable determination of the fatigue limit. Based on results obtained with this rapid testing method, the most suitable heat treatment to mitigate fatigue notch sensitivity and then achieving the best fatigue performance for chassis applications is discussed.